On Similative Reduplication in Vietnamese - Tue Trinh (Languages, 2025)
Vietnamese has a productive reduplication strategy where the reduplicant appears to the right of the base and is segmentally identical to the base except that its last rime is iếc (pronounced [ɪək]). In this note, I attempt to account for some observations about iếc, including the fact that it gives rise to ignorance inferences and is incompatible with classifiers. I propose that the semantics of iếc parallel the pragmatics of disjunctions and that the notion of similarity underlying the interpretation of iếc is contextual while that underlying the interpretation of classifiers is grammatical. The proposal makes use of some tools of predicate logic and formal semantics.